Analysis of deletion polymorphism of xenobiotics detoxication system genes in patients with tuberculosis and diabetes mellitus - Ihor Semianiv; Yuriy Sukholytkyi (Kazimierz Wielki University, 2022)
An analysis of the occurrence of alleles and genotypes of GSTM1 gene in patients with pulmonary tuberculosis and diabetes mellitus regarding the MBT resistance version allowed to establish that under the conditions of pulmonary tuberculosis infection GSTM1 gene deletion mutation can be found in one out of five (21.87% of cases), and the occurrence due to the MBT resistance version is: with NDTB - 17.39%, with MDR-TB 35.0%  and - PRTB 20.0% respectively. According to the nature of the distribution of allelic gene GSTM1 a favorable functional 1 allele prevails (73.29%) in the normal inbreeding among patients and deficiency of heterozygosity among healthy people, which generally forms a normal population distribution for the European race. Material and methods. The study involved 100 patients with newly diagnosed pulmonary TB and diabetes mellitus who had been hospitalized in Chernivtsi Regional TB Dispensary. The control group consisted of 50 healthy individuals. Genomic DNA was isolated from the whole venous blood. GSTM1 polymorphic areas were isolated by means of multicomplex polymerase chain reaction, according to the protocol for instantaneous analysis of polymorphism by M. Arana et all (1996). Deletion of gene corresponds to the lack of appropriate strips in the electropherogram. Results and discussion. Despite the fact that the activity of the enzyme glutathione-S-transferase of class M is encoded by five GST genes of class M (M1-M5), the dominant cause of genetically caused dysregulation of antioxidant activity is deletion (null) polymorphism of the gene GSTM1. Conclusion. Among the patients with pulmonary tuberculosis and diabetes mellitus one out of five persons (21,87 % of cases) was diagnosed with deletion mutation of GSTM1 gene; and the occurrence due to MBT resistance variation is: in NDTB-17,39 %, in MDR-TB - 35,0 % and in PRTB- 20,0 % respectively.